Аналіз сучасних діелектричних матеріалів та перспективи їх використання в мікросмужкових сенсорах гігагерцового діапазону - Чикун, Р. С. (ХНУРЕ, 2025)
This study examines dielectric materials for microstrip sensors operating in the gigahertz range (1–100 GHz), focusing on their impact on sensitivity, losses, and stability. Traditional materials like FR-4 and alumina (Al₂O₃) are compared with advanced low-loss polymers (PTFE, Rogers 4350B), metamaterials, and nanomaterials. The analysis highlights that while FR-4 has high losses, modern materials enhance impedance matching, minimize attenuation, and improve sensor performance in high-frequency applications.
Keywords: мікросмужковий сенсор; microstrip sensors